Species Delimitation In Rhabdosciadium (Apiaceae): Morphological and Molecular - Mehri, Shahram; Kolbadi, Iman; Shirafkan-Ajirlou, Hassan (Phytotaxa, 2020)
Rhabdosciadium is a distinct and small Apiaceae genus represented by only 8 species worldwide, 5 of which are distributed in Turkey and 3 occur in Iran. They all are narrow endemic, rare mountain species. The genus is characterized by single-fruited umbellules, linear-cylindrical fruits, parennial, glabrous, and junciform habit, reduced cauline leaves, and fibrous collar at the base of the stem. Till present time, there has been no detailed information available on molecular phylogeny and genetic structure of these species in the country. Therefore, the present study was conducted with the aim to investigate species delimitation by both morphological and molecular data and to reveal genetic diversity and population structure in these three Rhabdosciadium species. For this study, 98 randomly collected plants from 15 geographical populations in Rhabdosciadium species were used. We encountered extensive within species genetic and morphological diversity. ISSR molecular markers could delimit the studied species. STRUCTURE analysis revealed the occurrence gene flow between these species. The Mantel test showed correlation between genetic distance and geographical distance of the populations studied. Phylogenetic tree was constructed based on ITS data set which separated out-groups from the studied species. Genetic affinity of the studied species have been discussed.